Proceso atención de enfermería en gestante de 31.5 semanas con placenta previa más acretismo placentario. - Sevillano Román, Jeremy Elías (2022)
Placenta previa is defined as the insertion of the same over the opening of the cervix, in the lower part of the uterus, and not in the upper part of it. In both pathologies, bleeding may be minimal or absent, but in placenta accreta, the expulsion of the placenta does not occur within 30 minutes after delivery of the fetus. The ideal to detect placenta previa and accreta are laboratory tests, transvaginal ultrasound and magnetic resonance imaging. Regarding the treatment for placenta previa, it is based on bleeding control, rest, early delivery, blood transfusion and pharmacological treatment. The following case study is focused on a patient with 31.5 weeks of gestation who presented a clinical picture ± 2 hours of evolution characterized by transvaginal bleeding of moderate intensity without the presence of clots, colic-type pain in the hypogastric area that radiates to the lumbosacral region moderate with a fetal heart rate of 155 beats per minute. We proceed to the elaboration of the nursing care process in order to apply optimal care using the Nanda, Nic and Noc taxonomies, to identify the dysfunctional patterns that are compromising the patient's health status, and thus meet the proposed objectives. in this clinical case study.